Penerapan Labelisasi Halal dan Digital Marketing untuk Meningkatkan Minat Beli Konsumen Otak-otak Bandeng Kabupaten Gresik - Karisma Wati; Maziyah Mazza Basya (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Otak-otak bandeng is one of the popular traditional foods in Gresik Regency. However, to increase consumer buying interest, it is necessary to carry out an effective marketing strategy. This study aims to determine the application of halal labeling and digital marketing in increasing consumer buying interest in milkfish bran in Gresik Regency. This research method uses a qualitative approach with observation, interviews, and documentation. The results showed that the application of halal labeling can increase consumer confidence in milkfish brain-brain products, while the application of digital marketing through social media can increase consumer awareness and buying interest. Thus, the application of halal labeling and digital marketing can be an effective marketing strategy to increase consumer buying interest in milkfish brains in Gresik Regency.